Euglycemic Diabetic Ketoacidosis in a Sedated Patient after Coronary Artery Bypass Grafting: A Case Report and Literature Review - Mohamad S. Alabdaljabar; Khaled M. Abdullah; Ali Almasood; Syed Salman Ali; Abdullah Ashmeg (Case Reports in Medicine)
Euglycemic diabetic ketoacidosis (EDKA) is a rare and serious adverse effect of sodium-glucose cotransporter 2 inhibitors (SGLT-2i). The diagnosis is challenging due to the rarity, nonspecific symptoms, and absence of the alarmingly high blood glucose levels, and thus, it could be initially missed resulting in delayed treatment. This is particularly important for sedated patients, as the absence of typical clinical signs and symptoms can obscure the diagnosis. We present the case of a patient with type 2 diabetes mellitus on empagliflozin who developed EDKA while sedated after coronary artery bypass grafting (CABG) despite stopping the medication 24 hours prior to surgery. We also summarize the current literature on EDKA after CABG. Physicians must be aware and maintain a high index of suspicion for the illness, especially in patients with T2DM taking SGLT-2i and undergoing a major operation such as CABG. Emergent treatment and multidisciplinary follow-up are needed to improve patient outcomes and mitigate complications. Physicians should also consider identifying the optimal time to discontinue SGLT-2i before major surgeries and possible ketone studies in such patients, especially those sedated following the surgery.